1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Determine the sum of the given series:

  1. Jul 22, 2014 #1
    1. The problem statement, all variables and given/known data

    Sum starting from n=1 to infinity for the expression, (3/4^(n-2))

    What the solutions manual has done is multiply the numerator and the denominator by 4.


    I don't know what they have done from here on:

    12 / (1 - 1/4)

    = 16

    Can someone explain the solution? Thank you.
  2. jcsd
  3. Jul 22, 2014 #2
    It's a geometric series.
  4. Jul 22, 2014 #3
    I'm having trouble seeing how to use the fact that it is a geometric series in the problem. Could you explain further?
  5. Jul 22, 2014 #4
    Do you have a formula for the sum of a geometric series?
  6. Jul 22, 2014 #5
    I know for a geometric series the formula is Sn = (a(1-r^n)) / 1-r and for an infinite geometric series S = a/1-r
  7. Jul 22, 2014 #6
    OK then ... does ##\frac{12}{1-\frac{1}{4}}## look like one of those forms?
  8. Jul 22, 2014 #7
    Well the rate is 4, and the first value, a, is 1/4. Also 12 fits no where into any of these formulas so 12/(1-1/4) doesn't look like either of the two formulas for geometric series.
  9. Jul 22, 2014 #8
    Oh wait they are treating the entire expression as a geometric series not just the denominator. Is that it? Give me a second to see then.
  10. Jul 22, 2014 #9
    Ok I get it now I am finally getting 16 as an answer. My question is now why don't they divide 16 by 4 to get the original value to which the series converges to. (because in the beginning they multiplied the entire expression by 4?)
  11. Jul 22, 2014 #10
    They multiplied both the numerator and denominator of the term inside the sum by 4, which is the same as multiplying the whole term inside the sum by 4/4=1. Multiplying by 1 doesn't change anything, so there is nothing to "undo". It goes $$\sum\limits_{n=1}^\infty\frac{3}{4^{n-2}}=\sum\limits_{n=1}^\infty1\cdot\frac{3}{4^{n-2}}=\sum\limits_{n=1}^\infty\frac{4}{4}\cdot\frac{3}{4^{n-2}}=\sum\limits_{n=1}^\infty\frac{12}{4^{n-1}}=\sum\limits_{n=1}^\infty12\cdot\frac{1}{4^{n-1}}=\sum\limits_{n=1}^\infty12\cdot(\frac{1}{4})^{n-1}$$ with the formula for the geometric series applied to the RHS.
    Everything's equal, so ...
  12. Jul 22, 2014 #11
    Oh yes that is true the constant that is being multiplied is 1 not 4, so it won't change anything. Thank you for your help throughout this process; it is greatly appreciated!
  13. Jul 22, 2014 #12


    User Avatar
    Science Advisor

    [tex]\sum_1^\infty \frac{3}{4^{n-2}}= \sum_1^{\infty} \frac{3}{16}\frac{1}{4^n}= \frac{3}{16}\sum_1^\infty \frac{1}{4^n}[/tex]

    BUT the formula for the sum of a geometric series: [tex]\sum_{n=0}^\infty a^n= \frac{1}{1- a}[/tex] starts with n= 0, not n= 1. There are two ways to handle that.
    1) factor a "1/4" out of the series:
    [tex]\frac{3}{64}\sum_{n=1}^\infty \frac{1}{4^{n-1}}= \frac{3}{64}\sum_{i= 0}^\infty \frac{1}{4^i}[/tex] where i= n-1.

    2) Do the entire geometric series from 0 to infinity, then subtract off the n= 0 term:
    [tex]\frac{3}{4}\sum_{n=0}^\infty \frac{1}{4^n}- \frac{3}{4}[/tex]
    since when n= 0, [tex]\frac{1}{4^n}= 1[/tex].
    Last edited by a moderator: Jul 22, 2014
  14. Jul 22, 2014 #13
    Some texts give ##\sum\limits_{n=1}^\infty ar^{n-1}=\frac{a}{1-r}## as (one of) the formula(s) for the geometric series. Given the answer from the solutions manual, I'm guessing the topic creator is using one of those texts.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted